Comparison of human mesenchymal stem cells derived from bone marrow, synovial fluid, adult dental pulp, and exfoliated deciduous tooth pulp. Issue 1 (January 2016) - Isobe, Y.; Koyama, N.; Nakao, K.; Osawa, K.; Ikeno, M.; Yamanaka, S.; Okubo, Y.; Fujimura, K.; Bessho, K.
Abstract: Populations of pluripotent stem cells were isolated from bone marrow, synovial fluid, adult dental pulp, and exfoliated deciduous teeth and their multipotentiality properties compared. Osteogenic, chondrogenic, adipogenic, and neurogenic differentiation potentials were examined. Bone marrow mesenchymal stem cells (BMMSCs) and synovial fluid-derived cells (SFCs) showed the highest levels of osteogenesis as expressed by alkaline phosphatase (ALP) activity (0.54 ± 0.094 U/mg protein and 0.57 ± 0.039 U/mg protein, respectively; P = 0.60) and by osteocalcin (BGLAP; determined by real-time RT-PCR). SFCs showed the highest levels of chondrogenesis as expressed by ALP activity (1.75 ± 0.097 U/mg protein) and of COL2A1 and COL10A1 by real-time PCR. In terms of adipogenesis, lipid vesicles were observed in the BMMSCs and SFCs. Dental pulp stem cells (DPSCs) and stem cells from human exfoliated deciduous teeth (SHED) exhibited neurogenesis potential, as shown by increases in expression of class III β-tubulin (TUBB3) and microtubule-associated protein 2 (MAP2) on RT-PCR. Variability was found in the differentiation potential corresponding to the tendency of the original tissue to differentiate. It is suggested that the cell type should be selected depending on the regenerative treatment regimen.